2015
DOI: 10.1007/s40596-015-0390-1
|View full text |Cite
|
Sign up to set email alerts
|

College Mental Health: A Vulnerable Population in an Environment with Systemic Deficiencies

Abstract: From time to time, attention is brought to the status of mental health-or, rather, mental illness-on US college campuses. We thank Michelle Riba, Daniel Kirsch, Adele Martel, and Michelle Goldsmith for guest editing a special collection of articles on this topic for this issue of the journal.A May 2015 article in the New York Times [1] reported that nearly one in six college students was diagnosed with or treated for anxiety within the previous 12 months. The article also pointed out that anxiety has surpassed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…This limited role is due in part to the overall crisis in college mental health, that is, the lack of adequate systems of care within US colleges and universities-including the absence of psychiatry services on many, especially smaller, campuses-in spite of the pervasive mental health issues that college students currently face [12]. When they are involved, psychiatrists primarily help the survivors of sexual violence with the aftermath of such an experience, yet the most important factor in a holistic social response to the epidemics of sexual violence on college campuses lies in primary prevention.…”
Section: The Role Of Academic Psychiatrymentioning
confidence: 99%
“…This limited role is due in part to the overall crisis in college mental health, that is, the lack of adequate systems of care within US colleges and universities-including the absence of psychiatry services on many, especially smaller, campuses-in spite of the pervasive mental health issues that college students currently face [12]. When they are involved, psychiatrists primarily help the survivors of sexual violence with the aftermath of such an experience, yet the most important factor in a holistic social response to the epidemics of sexual violence on college campuses lies in primary prevention.…”
Section: The Role Of Academic Psychiatrymentioning
confidence: 99%
“…The varying effects of meditation and breathing may be evident in novice yoga exercisers such as undergraduate students; however, this assumption needs to be tested through empirical evidence. Most undergraduate students have little to no experience of practicing yoga exercise, and they are considered a vulnerable population for mental health (Balon et al, 2015). Engaging in considerable mental work daily, undergraduates would need to accumulate mental resources and alertness at work and to focus.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several studies indicated an age-related decline in the level of PA throughout life and that the PA pattern in adolescence usually affected the pattern in adulthood [6][7][8][9]. Despite the importance of regular PA, many university students are now living in an environment with increased barriers to PA, resulting in a lack of adequate physical exercise and a failure to develop PA behaviors [10][11][12][13]. The 2014 National Physique Monitoring Bulletin released by the General Administration of Sport of China indicated that Chinese university student physical fitness has continued to decline [14].…”
Section: Introductionmentioning
confidence: 99%